Observations of convection in the dayside magnetosphere by the beam instrument on Geotail - H. Matsui; H. Matsui; M. Nakamura; T. Mukai; K. Tsuruda; H. Hayakawa (Annales Geophysicae, 2001)
We report observations of magnetospheric convection by the beam instrument, EFD-B, on Geotail. The region analyzed in this study is mainly the afternoon sector of the magnetosphere between L = 9.7 - 11.5. When the instrument is operated, electron beams are emitted from guns and some of them return to detectors attached to the main body of the satellite. However, we find that the return beams are often spread over a wide range of satellite spin phase angles, so that the calculated convection is unreliable. In order to remove noisy data, we set up suitable selection criteria. We infer that the convection strength is of the order of 20 km/s. The convection has generally westward and outward components. This indicates that the plasma located at the satellite positions is being convected toward the magnetopause. Moreover, the obtained convection is highly variable because standard deviations are comparable to the strength. We then compare the convection estimated by the beam instrument with that by the particle instrument, LEP. We find that the convections derived from the two instruments are positively correlated, with correlation coefficients above 0.7. The analysis reported here is expected to be useful in the interpretation of the multi-spacecraft data from the Cluster II mission. Key words. Magnetospheric physics (current systems; electric fields; instruments and techniques)